Common Media Used in Hydroponics - Morgan Pinkerton; Brianna Whitman; Hannah Wooten; Celina Gomez (EDIS, 2022)
Hydroponics is a method of growing plants without using soil. In hydroponics, plants can be grown either directly in a nutrient solution (water-culture) or in an inert media (media-culture). In media-culture, the type of media is critical to the success of plant production. Designed for hydroponic beginners, this new 5-page publication of the UF/IFAS Environmental Horticulture Department will cover the basic properties of media and specifically discuss media commonly used in hydroponics. Written by Morgan Pinkerton, Brianna Whitman, Hannah Wooten, and Celina Gomez. https://edis.ifas.ufl.edu/ep623